The effect of time-varying fundamentals in learning-to-forecast experiments - Alfarano, Simone; Camacho-Cuena, Eva; Colasante, Annarita; Ruiz-Buforn, Alba (Journal of economic interaction and coordination, 2024)
Inspired by macroeconomic scenarios, we aim to experimentally investigate the evolution of short- and long-run expectations under different specifications of the fundamentals. We collect individual predictions for future prices in a series of Learning to Forecast Experiments with a time-varying fundamental value. In particular, we observe how expectations evolve in markets where the fundamental value follows either a V-shaped or an inverse V-shaped pattern. These conditions are compared with markets characterized by a constant and a slightly linear increasing fundamental value. We assess whether minor but systematic variations in the fundamentals affect individual short- and long-run expectations by considering positive and negative feedback-expectation systems. Compared to a setting with constant fundamentals, the slowly varying fundamentals have a limited impact on how subjects form their expectations in positive feedback markets, whereas in negative feedback markets we observe notable changes.